성인 알코올사용장애 환자에서 주의력결핍 과잉행동 증상 유무에 따른 임상적 및 신경심리학적 특성 - 조정민(Jung Min Jo); 이동준(Dong Jun Lee); 정경희(Kyung Hi Jung); 오송인(Song In Oh); 안동현(Dong Hyun Ahn) (Soa--chʻŏngsonyŏn chŏngsin ŭihak = Journal of child & adolescent psychiatry, 2014)
Objectives : Alcohol use disorder (AUD) is often comorbid with adult attention-deficit hyperactivity disorder (ADHD) and other psychiatric illnesses. When associated with other mental problems, the prognosis of the AUD can be more serious. This study shows research on the clinical and neuropsychological characteristics according to whether or not ADHD symptoms and AUD were comorbid. Methods : A total of 64 adult inpatients who completed AUD scales about adult ADHD, alcohol dependence, depression, anxiety, and impulsiveness. They also completed neuropsychological tests about attention and executive function. According to the Adult ADHD Self-Report Scale score, patients were categorized into two groups (ADHD symptom positive/negative group). Results : Fourteen among the 64 subjects were part of the ADHD symptom positive group (21.9%). They had statistically significant shorter abstinence periods and a higher rate of history of 'rule violation during school' and 'physical damage in childhood' compared to the ADHD symptom negative group. Conclusion : The comorbidity rate with ADHD symptom in adult AUD is higher than the general population. The ADHD symptom positive group suffered from more severe and refractory AUD. Considering the more frequent history of rule violation during school in the ADHD symptom positive group, the association between ADHD and AUD may be mediated by conduct disorder. Therefore we suggest the necessity of careful evaluation and intervention in children and adolescents with ADHD and conduct disorder.